Қазақ прозасында құбылыс болған шығармалар сыры (Төлен Әбдікұлының «Оң қол», «Парасат майданы» шығармалары бойынша) - Лекерова, Е.Ж. (My University, 2013)
This article examines the work of the winner of the state award, the writer Tolen abdikova "right hand man," and "Parasat Maidan. researchers analyzed by academics and literary critics of the data products.